Implementation of the project-based learning model to improve sefl efficacy and student learning outcomes - Muhammad Wahyu Setiyadi (Jurnal Pijar Mipa, 2023)
This study aimed to determine the application of the project-based learning model to self-efficacy and student learning outcomes in the botany Phanerogamae course. The research method used in this study is the PTK method or Classroom Action Research. The subjects in this study are students of the Biology Education study program STKIP Al Amin Dompu, even in the semester 2022/2023. The instruments used in this study are lumbar instruments of student self-efficacy and instruments of student learning outcomes. The analysis used in this study is qualitative descriptive analysis. The results showed that applying the project-based learning model can improve student learning outcomes and self-efficacy. The self-efficacy of students in the botany Phanerogamae course in the pre-cycle was 49.12%; in the first cycle, it was 78.95%, and in the second cycle, it was 91.23%. Meanwhile, student learning outcomes have also improved. In the pre-cycle, it was 47.37%, cycle I was 78.95%, and cycle II was 89.47%.